2020
DOI: 10.1007/s00384-020-03567-1
|View full text |Cite
|
Sign up to set email alerts
|

HPV-associated anal lesions in HIV+ patients: long-term results regarding quality of life

Abstract: Purpose HIV infection and concomitant HPV-associated anal lesions may significantly impact on patients' quality of life (QoL), as they are predicted to have negative effects on health, psyche, and sexuality. Material and methods Fifty-two HIV+ patients with HPV-associated anal lesions were enrolled in a survey approach after undergoing routine proctologic assessment and therapy for HPV-associated anal lesions if indicated over a time span of 11 years (11/2004-11/2015). Therapy consisted of surgical ablation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In relation to sexuality, the attitudes of our participants were variable, as also described elsewhere in the literature. 17,27 Most described changes in their sexual practices after AC screening, as also previously described among people with and without HIV infection with anal HPV lesions 27,41 and in women with cervical cancer and HPV. 42 Nonetheless, some participants did not change their sexual habits for more than the recommended 2 to 3 days after screening.…”
Section: N Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In relation to sexuality, the attitudes of our participants were variable, as also described elsewhere in the literature. 17,27 Most described changes in their sexual practices after AC screening, as also previously described among people with and without HIV infection with anal HPV lesions 27,41 and in women with cervical cancer and HPV. 42 Nonetheless, some participants did not change their sexual habits for more than the recommended 2 to 3 days after screening.…”
Section: N Discussionmentioning
confidence: 65%
“…Moreover, the results so far obtained are disparate. After screening, some studies reported decreased subjective sexual pleasure along with avoidance of sexual contact 27 or feelings of guilt about acquiring HPV as the result of sustained sexual practices 28 . However, other studies observed that being included in AC prevention programs did not universally affect the sexuality of the participants 17 .…”
mentioning
confidence: 99%